2019
DOI: 10.1177/0021998319857463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondary bending and bolt load on damage and strength of composite single-lap interference-fit bolted structures

Abstract: The single-lap interference-fit bolted joint is widely used in composite structures. In order to get an accurate prediction of bearing strength, secondary bending and bolt load effects are studied in the present research via combination of experimental and numerical methods. The joint specimens with four levels of interference-fit size ( I) and bolt torque ( T) were tested according to ASTM standard D5961 to evaluate the bearing behavior and joint stiffness. Meanwhile, a finite element model considering the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The effect of preload on the mechanical properties of composite structures has also been studied by many scholars. Zhang et al 30 studied the influence of interference-fit size and bolt torque on the mechanical properties of composite single-lap joints. It claimed that the bearing strength of composite joints is more sensitive to bolt torque.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The effect of preload on the mechanical properties of composite structures has also been studied by many scholars. Zhang et al 30 studied the influence of interference-fit size and bolt torque on the mechanical properties of composite single-lap joints. It claimed that the bearing strength of composite joints is more sensitive to bolt torque.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The damage modes and failure mechanisms of the specimens were analyzed by observing the cross‐section morphology. Zhang studied the effect of the coupling of hole perpendicularity error and delamination defects on the damage mode and stress distribution of bolt joints and concluded that the hole perpendicularity error affects the secondary bending effect of the joints, which in turn can affect the stress state at the edge of the hole and the failure mode of the specimen (Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers analyzed the comprehensive impact of the interference associated torque for CFRP joints. Zhang et al 22 identified the optimal interference-fit and torque by combing experimental and numerical methods; however, the research did not consider the impact of the preload imbalance. Hu et al 23,24 investigated the mechanism of bolt pre-tightening and preload relaxation in composite interference-fit joint structures, and identified a frictional force.…”
Section: Introductionmentioning
confidence: 99%